Elevated fecal levels of eosinophil granule proteins predict collagenous colitis in patients referred to colonoscopy due to chronic non-bloody diarrhea. (2nd July 2016) - Wagner, Michael; Sjöberg, Klas; Vigren, Lina; Olesen, Martin; Benoni, Cecilia; Toth, Ervin; Carlson, Marie
Abstract: Objective: Colonoscopy with biopsy sampling is often performed to detect collagenous colitis (CC) and lymphocytic colitis (LC) in patients with chronic non-bloody diarrhea. However, the diagnostic yield is low and incurs high costs. Fecal calprotectin (FC) and myeloperoxidase (MPO) indicate intestinal inflammation in ulcerative colitis (UC) and Crohn's disease (CD). In CC, elevated fecal levels of eosinophil protein X (EPX) and eosinophil cationic protein (ECP) have been reported. We aimed to evaluate if F-EPX, F-ECP, FC, and F-MPO could predict the diagnostic outcome in patients with chronic non-bloody diarrhea referred to colonoscopy. We also evaluated serum (S) EPX and ECP in this regard. Methods: Of 67 included patients, 63 (94%) underwent colonoscopy with biopsy sampling. Fecal EPX, F-ECP, FC, F-MPO, S-EPX, and S-ECP were analyzed. Results: Diagnostic outcome: normal: n  = 46 (73%), CC: n  = 9 (14%), LC: n  = 4 (6%), UC: n  = 2 (3%), CD: n  = 2 (3%). Higher levels of F-EPX and F-ECP were found in CC compared to a normal diagnostic outcome ( p  = 0.01). No change was noted in any of the fecal markers in LC. When all of the fecal markers were normal the probability of a normal diagnostic outcome was 92%. We found no differences in S-EPX and S-ECP between the groups. Conclusion: Elevated F-EPX and F-ECP could predict CC. None of the fecal markers predicted LC. Serum-EPX and S-ECP are not useful for the diagnosis of CC, LC, UC, or CD. With normal levels in all of the analyzed fecal markers, there is a low probability of a pathologic diagnostic outcome.